Systematic review and classification of: Olweus Bullying Prevention Program (OBPP) – A School-Wide Program Against Bullying and Antisocial Behavior (2. ed.) - Havik, Trude; Ertesvåg, Sigrun (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2020)
Background: The Olweus Bully Prevention Program (OBPP) aims to reduce bullying and anti-social behavior in primary and lower secondary school, by creating safe and good learning environment for all students. This article is a summary of knowledge about the effects of the preventive and schoolwide OBPP in primary school, whether the measure is effective and recommended for use in Norwegian schools. Method: This knowledge summary is based on systematic literature searches in various databases such as Embase, Medline, Psykinfo, Norart, Cochrane, Cristin, Nora, Scopus, Campbell and Blueprint. In addition, information is obtained from the owner of OBPP. Results: Six Norwegian effect studies, three separate effect studies from the US and two independent studies from the US, two international meta-analyzes and an international evaluation (Blueprint, which shows that OPBB meets the requirements for a Blueprint or model program) were identified. These results include an assessment of the program's description, impact studies, quality of research methods and quality of implementation. The program is well described and has a comprehensive system for enhancing implementation quality. The effect of OBPP is well described and documented. At the same time, Norwegian effect studies must to a greater extent meet today's required documentation, with a broader age composition and larger sections of the students in primary school and several independent studies, could strengthen the documentation. However, these results must be related to the development and implementation of OBPP, and to the establishment of a new field of research and represents work back to the 1970s. Conclusion: According to the criteria for Ungsinn.no, OPBB is classified as a documented effective measure at evidence level 5: Interventions with strong documentation of effect.